Putting values-based leadership into practice : readings of Jansen Kraemer - Diachenko, Kristina (2018)
Values-based leadership (VBL) is quite an unexplored area in the leadership theory, despite of the fact that values are present and mentioned almost in all main leadership approaches. The purpose of the study is to investigate practical solutions for putting principles of VBL into actions. This purpose is met by investigating the leadership experiences of Jansen Kraemer that he described in his two books: “From values to action: the four principles of values-based leadership” (2011), and “Becoming your best: bring values-based leadership to all that you do” (2015). Those books were used as a data for the present study. In order to answer the research questions, the qualitative method was used, and the data extracted from the books by Jansen Kraemer was analysed using the content analysis. The data was explored specifically with the focus on the research questions. The findings show that Jansen Kraemer defines VBL through the source of VBL, the aim, and followers. VBL is also seen as a philosophy. The practical ways to implement VBL approach are: culture creation, communication with the team, finding meaning and purpose in what you are doing, and focusing on the right thing to do. As for the characteristics of values-based leader, that person is treated as a role model for everyone in the organization, being a values-based leader is a broader calling that goes beyond a job position. Values-based leaders are also perceived by Jansen Kraemer through their personality traits and their performance at work. The study focuses on exploring Jansen Kraemer’s understanding of practice of VBL approach, which broadens the range of leadership tools that can be used.